Beliefs and Attitudes of Consumers At Online Merchants In Predicting Purchase Intention - Teguh Wicaksono; Syahrani Syahrani; Defin Shahrial Putra; Abdurrahim Abdurrahim (At-Tadbir : jurnal ilmiah manajemen, 2023)
Consumer trust in sellers in the marketplace not only affects their trust in others, but also affects the way consumers make online purchases. This study intends to explain the relationship between consumer trust and other predictors that can increase a person's willingness to make online purchases in the marketplace. This study used quantitative methods and questionnaires as research instruments with a total sample of 138 respondents with the criteria of having made an online purchase at least 2 times in the last 3 months, the data were analyzed using PLS-SEM. The findings show: (1) consumers' attitudes to online purchase intention have a greater impact when compared to consumer confidence, (2) the role of attitude variable mediation can increase online purchase intention. The results showed the importance of increasing one's trust in the transaction process that takes place in online sales and it makes consumers feel comfortable and causes liking with online shopping which ultimately increases one's desire to make purchases online in the marketplace.